2020
DOI: 10.3390/ijerph17093030
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Tolerability of a Culture-Based Virtual Reality (VR) Training Program in Patients with Mild Cognitive Impairment: A Randomized Controlled Pilot Study

Abstract: The present study examined whether a culture-based virtual reality (VR) training program is feasible and tolerable for patients with amnestic mild cognitive impairment (aMCI), and whether it could improve cognitive function in these patients. Twenty-one outpatients with aMCI were randomized to either the VR-based training group or the control group in a 1:1 ratio. The VR-based training group participated in training for 30 min/day, two days/week, for three months (24 times). The VR-based program was designed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 28 publications
(24 reference statements)
1
59
0
Order By: Relevance
“…The overall attrition rate of both VRCT and CBCT was satisfactory (all less than 20%), except the CBCT study done by Finn and McDonald (2012) recorded a 33% attrition rate. The attrition rate ranged from 0% [25] to 33% [15], though dropout rate was not specified in some studies [22,23,[26][27][28][29][30]. The primary reason for dropouts was mainly independent of the intervention, such as unrelated medical or personal issues [15,[31][32][33][34].…”
Section: Compliance and Attrition Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall attrition rate of both VRCT and CBCT was satisfactory (all less than 20%), except the CBCT study done by Finn and McDonald (2012) recorded a 33% attrition rate. The attrition rate ranged from 0% [25] to 33% [15], though dropout rate was not specified in some studies [22,23,[26][27][28][29][30]. The primary reason for dropouts was mainly independent of the intervention, such as unrelated medical or personal issues [15,[31][32][33][34].…”
Section: Compliance and Attrition Factorsmentioning
confidence: 99%
“…This may be explained by the content and immersiveness of VRCT [29,[32][33][34] e.g., home-setting, grocery shopping and taking public transport). Moreover, VR promotes cognition by enabling real-life experiences, new learning opportunities, and engagement [30,35]. VR helps to reenact past activities (e.g., visiting museum, going to firework party) in which individuals with MCI within aged care may not be able to join physically [30,35].…”
Section: Effectiveness Of Cbct and Vrctmentioning
confidence: 99%
“…VR facilitates the creation of a multisensory, dynamic, interactive virtual environment with a great similarity to real life [16]. In addition, VRCR is intuitive, interesting, and fun, promoting active participation by enhancing motivation for rehabilitation [17,18]. Several studies have reported that the application of exergame increases the motivation of the elderlies [19] and helps improve the cognitive function in MCI patients [20].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike us, they reported AE such as dizziness and fatigue during the intervention in the VR group [81]. They also measured participants' depression symptoms with 15-item Korean version of GDS [82] and reported an improvement (week 12 score-baseline score=1.1, 95% CI, -0.87 to 3.07) [81].…”
Section: Discussionmentioning
confidence: 90%
“…A recent pilot randomized control trial in older adults (71.8 ±6.6) without dementia (n=24) used VR games with headset (30 min/day, two days/week for three months) to explore its feasibility [81]. Similar to us, they declared that VR experience is feasible for older adults (adherence rate was 91.55% ±6.41%) in the VR group [81]. Unlike us, they reported AE such as dizziness and fatigue during the intervention in the VR group [81].…”
Section: Discussionmentioning
confidence: 99%